Analytical Study of Water Purity Using Low Power He:Ne Laser - Mohammed, Mohammed F.; Matti, Dina J. (Nahrain University College of Engineering Journal, 2011)
In this research, an analytical study of water using laser source transport through some samples of water tubes was presented. He Ne laser with measured maximum output power 2.83 mW was used to determine the purity of water by measuring its output power when it was passing through tube of water. This tube was initially filled by water and then by distill water contain different ratio of salts and clay. For each case, the output power would be measured and calculated its attenuation which was occurred when laser was passing through the water. The attenuation happened in the laser beam when transport through the water ample that contain NaCl due to the absorption process. The attenuation happened in the laser beam when transport through the water sample that contain clay due to the scattering process. Water tap mostly contain different ratio of salts and clay so the attenuation accurse in laser beam is due to absorption andscattering process, and it can be compared these results with that produce when mixing NaCl solution sample with the clay sample.